IMPACT ENVIRONNEMENTAL DE LA ZONE INDUSTRIALO-PORTUAIRE (ZIP) D’ABIDJAN - Kablan N’guessan Hassy Joseph; Kouakou N’goran Norbert (European Scientific Journal, ESJ, 2013)
This study attempts to assess the impact of the industrial port area of Abidjan on the environment. The results highlight the positive and negative aspects of the activities of MIDAS. On one side, the port attracts factories in Abidjan at the expense of other localities in order to maximize profit in exchange for royalties it collects for services rendered. On the other hand, industrial facilities hamper the flow of traffic, but also discharge effluents that are poorly managed. Therefore, when the geographical phenomena (winds) combine with pollution from factories, local populations are exposed to many diseases, especially cardiovascular, the lagoon environment also suffers damage.